Integrative social cognition remediation with social skills training for adults: PICSIS – pilot study in autism and schizophrenia - Visser, Maxime; Béasse, Amandine; El Gholabzouri, Hala; Chenault, Marie; Didou, Josselin; Kostova, Milena; Morvan, Yannick; Mendy, Mauricette; Amado, Isabelle; Moualla, Mona (Frontiers in Psychiatry, 2026)
Autism spectrum disorder (ASD) and schizophrenia share neurodevelopmental alterations, particularly deficits in social cognition (SC) that strongly influence social and functional outcomes. Although social cognition remediation (SCR) and social skills training (SST) have each shown efficacy, no validated intervention yet integrates both approaches. This open-label, prospective study examined the feasibility and preliminary effects of PICSIS (Programme Intégratif de remédiation de la Cognition Sociale et d’Interaction Sociale), a group-based program alternating 19 SCR and 11 SST sessions over 30 biweekly sessions. Eighteen clinically stable adults with ASD or schizophrenia (mean age = 35.8 ± 9.3 years) completed the intervention. Feasibility was assessed through attendance and dropout rates; clinical, cognitive, and functional outcomes were evaluated pre- and post-intervention using validated French instruments (ClaCoS battery, ERF-CS, GAF, BPRS). Attendance was high (89.4%), confirming feasibility. While clinical symptoms and global functioning did not significantly change, participants showed significant improvements in theory of mind (MASC, p = 0.033, r = 0.61), reduced hostility attribution bias (AIHQ, p = 0.009, r = 0.82), and fewer self-reported SC complaints (ACSo, p = 0.0037, r = 0.89). Functional outcomes exhibited positive, non-significant trends. These preliminary findings indicate that PICSIS is feasible, well tolerated, and associated with specific social cognitive benefits across diagnostic categories. Further randomized controlled studies with larger samples are warranted to confirm its efficacy and long-term impact.